Fake Graduates - Sorooshian, Shahryar (Springer Netherlands, 2017)
There is growing concern regarding the erosion of industries’ trust in the reliability and validity of university graduates. Fake graduates are described in this letter. This article endeavors to warn of a new version of the scholarly black market, in which theses and dissertations are sold to students seeking to graduate under false pretenses.